USEING OF COMET ASSAY FOR DETECTION OF THE DAMAGE IN DNA DUE TO THE INFECTION BY BLOOD PARASITES IN CYRUS GOAT KIDS - & et al., Al-Samarai (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
This study was carried out at the Ruminants Researches Station (20 km west of Baghdad) /State Board for Agriculture Researches / Ministry of Agriculture, and Biotechnology Research Center of AL-Nahrain University  during 1/8/213 to 1/8/2014. The aim of this study was to identify the damage in DNA according to comet assay procedure, after testing of 50 infected goat kids with blood parasites. Most of traits affected significantly by infection, as most of traits showed a depression due to infection.  The results revealed that the effect of type on the traits of comet assay was significant (P < 0.01) in this research. The infected goat kids were surpassed the corresponding healty goat kids for all measures of comet, whereas, the healty goat kids surpassed the corresponding infected goat kids